BIOLOGICAL AGENTS AND THEIR ROLE TO INCREASE PLANT ESSENTIAL OIL UNDER WATER STRESS Agen Hayati dan Peranannya dalam Meningkatkan Minyak Atsiri Tanaman pada Kondisi Cekaman Air - Agus Prayitno Kurniawan; Nurul Aini Aini; Moch Dawam Maghfoer; Wiwin Sumiya Dwi Yamika; Restu Rizkyta Kusuma (Puslitbang Perkebunan, 2021)
Essential oils are plant natural products resulting from secondary metabolites used for raw materials of various industries such as perfumery, preservative, cosmetics, and pesticide. The major problem of essential oil plants cultivation is the low essential oil content. Enhancing essential oil content is one of the main focuses in developing essential oil plants which can be reached by water management. Growth and yield reduction and changes in some physiological reactions are the responses of a plant toward water supply shortage (water stress). Water stress triggers elicitors and some signal molecules produced for secondary metabolites resulting in higher essential oil percentages. However, it would also decrease essential oil yield following lower biomass production. Some microorganisms can produce phytohormone and enhance nutrient uptake allowing the plant to cope under water stress condition. Understanding how the environment affected plant secondary metabolite (especially essential oil), as well as microorganism roles for crop production, will provide proper cultivation technology to increase plant essential oil content and oil yield. This review aimed to analyze the potential use of some biological agents to alleviate the negative effect of water stress on essential oil plants.ABSTRAKMinyak atsiri merupakan produk alami tanaman dari hasil metabolisme sekunder yang digunakan sebagai bahan baku berbagai industri seperti parfum, antiseptik, kosmetik, dan pestisida. Budidaya tanaman minyak atsiri menghadapi kendala seperti rendahnya kandungan minyak yang dihasilkan. Pertumbuhan dan penurunan hasil serta perubahan pada beberapa reaksi fisiologis merupakan respon tanaman terhadap cekaman air. Cekaman air memicu produksi elisitor dan beberapa molekul sinyal pada metabolit sekunder sehingga dapat menghasilkan minyak atsiri yang lebih tinggi, akan tetapi tidak diikuti dengan peningkatan produksi biomassa sehingga produksi minyak atsiri tidak cukup tinggi. Beberapa mikroorganisme mampu menghasilkan fitohormon dan meningkatkan serapan hara yang memungkinkan tanaman dapat bertahan pada kondisi cekaman air. Pemahaman bagaimana lingkungan dapat mempengaruhi metabolit sekunder dari tanaman (khususnya minyak atsiri), serta peran mikroorganisme terhadap produksi tanaman, akan menghasilkan teknologi budidaya yang sesuai untuk meningkatkan kandungan dan hasil minyak atsiri suatu tanaman. Review ini bertujuan menganalisa potensi penggunaan beberapa jenis agens hayati untuk mengurangi dampak negatif dari cekaman air pada tanaman penghasil minyak atsiri.